STRATEGI PEMASARAN, MODAL USAHA DAN TEKNOLOGI BUDIDAYA TERHADAP PENINGKATAN PENDAPATAN PETAMBAK UDANG VANAME DI KECAMATAN TURI LAMONGAN - Imtinan Widhah Kumala (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
Indonesia's aquaculture sector continues to play a strategic role in enhancing coastal community welfare, particularly through the cultivation of vannamei shrimp (Litopenaeus vannamei). In recent years, Lamongan Regency—specifically Turi District—has emerged as a prominent shrimp farming center in East Java. However, the physical expansion of shrimp farming has not been matched by a significant improvement in the income of small and medium-scale farmers. This study aims to examine the effect of marketing strategies, business capital, and cultivation technology adoption on farmers' income in vannamei shrimp farming. The research uses an explanatory approach involving 73 respondents selected through purposive sampling. Data were collected via structured questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method through SmartPLS 3. The results show that all independent variables have a significant effect on income, both partially and simultaneously. Business capital has the most dominant influence (β = 0.379), followed by marketing strategy (β = 0.341), and cultivation technology (β = 0.312). The model explains 65.2% of the variance in income (R² = 0.652). This study contributes to the literature by integrating marketing, financial access, and technology variables within a localized aquaculture development model. The findings are expected to inform regional policy planning to improve the productivity and welfare of small-scale shrimp farmers.